Risk Assessment of Toxic Elements in Fruits and Vegetables Grown in Ararat Region, Armenia - Pipoyan, D. A.; Beglaryan, M. R.; Tepanosyan, G. H.; Sahakyan, L. V. (ՀԱԱՀ հիմնադրամ)
This study aims to assess toxic elements’ contents in fresh fruit and vegetable, as well as related potential health risks to the adult population in the Ararat region. In the frame of the research, the transfer of toxic elements from soil to plants was evaluated and non-carcinogenic risks from food consumption were assessed. The results indicated that only in the case of apple consumption there is a low level of non-carcinogenic risk to As exposure. Meanwhile, in multifood consumption and multi-element ingestion cases, the low level of risk was reported both for As and Pb exposure. Further comprehensive assessments considering more elements and additional routes of exposure are needed in the region.
Keywords: Food Science and Technology